2016
DOI: 10.1021/acs.accounts.6b00193
|View full text |Cite
|
Sign up to set email alerts
|

Identifying N-Glycan Biomarkers in Colorectal Cancer by Mass Spectrometry

Abstract: Colorectal cancer (CRC) is one of the most prevalent cancers worldwide. Delineating biological markers (biomarkers) for early detection, when treatment is most effective, is key to prevention and long-term survival of patients. Development of reliable biomarkers requires an increased understanding of the CRC biology and the underlying molecular and cellular mechanisms of the disease. With recent advances in new technologies and approaches, tremendous efforts have been put in proteomics and genomics fields to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
4
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 82 publications
(121 reference statements)
3
49
4
1
Order By: Relevance
“…To study the influence of aging, two old‐aged groups were formed, up to and above 80 years old, and in each group two subgroups were defined: male and female. Two groups of patients and their hTf were included in the study as well, as it was reported that both T2DM and CRC may alter protein glycosylation . The results for interactions between hTf molecules of different origin and six most reactive lectins are shown in Figure and statistical analysis of the data (at the level of technical replicates needed for obtaining the information on the reproducibility of the created analytical platform …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To study the influence of aging, two old‐aged groups were formed, up to and above 80 years old, and in each group two subgroups were defined: male and female. Two groups of patients and their hTf were included in the study as well, as it was reported that both T2DM and CRC may alter protein glycosylation . The results for interactions between hTf molecules of different origin and six most reactive lectins are shown in Figure and statistical analysis of the data (at the level of technical replicates needed for obtaining the information on the reproducibility of the created analytical platform …”
Section: Resultsmentioning
confidence: 99%
“…This finding is also in accordance with the results of Qiu et al [9] who reported an increase in core fucosylation of several serum proteins due to colon cancer, such as complement C3, histidine-rich glycoprotein, and kininogen-1. [11,38,51,52]…”
Section: Application Of Lectin-based Protein Microarray For the Analymentioning
confidence: 99%
See 1 more Smart Citation
“…Several CRC tissue-associated changes in glycans have been reported and recently reviewed. 15 Holst et al 16 showed pronounced differences between the N -glycosylation patterns of CRC cell lines, and CRC cell line profiles differed from tissue-derived N -glycan profiles. Osuga et al 17 found that increased fucosylation was correlated with metastatic potential in CRC.…”
mentioning
confidence: 99%
“…PGC stationary phase in LC-MS was used by Sethi et al to determine the reduced N-glycans on cell membrane from cell lines of colorectal cancer. 64 In the study, increase of high mannose glycans and α(2,6)-sialylation was observed for the cancer. Song et al has used this method to determine the relative abundances of N-glycans released from serum (Figure 6) as well as biological variations between individuals.…”
Section: Methods For Profiling Glycans and Glycoprotein Cancer Markersmentioning
confidence: 81%